Analisa Pengaruh Citra Merek Dan Kualitas Produkterhadap Keputusan Pembelian (Studi Kasus Pasta Gigi Nasa Di Wilayah Kota Sumbawa Besar) - Risia, Aulia Febrina; Henny, Henny (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The purpose of this study was to determine: (1) the influence of brand image on NASA toothpaste purchasing decisions, (2) the effect of product quality on NASA toothpaste purchasing decisions, and (3) influence of brand image and product quality on NASA toothpaste purchasing decisions. In this study using the independent variable brand image (x1) and product quality (x2). The analytical method used is multiple linear regression analysis. The samples used in this study were 60 respondents taken randomly from NASA toothpaste consumers who made purchasing decisions. The data obtained is primary data which is the result of respondents' answers to the questionnaire distributed. The results of this study indicate that: (1) brand image has a positive effect on purchasing decisions, evidenced by the value of tcount of 4.606 with a significance value of 0.000, smaller than 0.05 and the regression coefficient has a positive value of 0.339; (2) product quality has a positive effect on purchasing decisions, as evidenced by the tcount of 6.273 with a significance value of 0.000, smaller than 0.05 and the regression coefficient has a positive value of 0.522, and simultaneous brand image and product quality have a positive influence on purchasing decisions, evidenced by the results of F count of 48,089 with a significance of 0,000.